Role of Doppler Ultrasound in Differentiation between Benign and Malignant Lymph Nodes - Alaa Abdelhakim Taha Ahmed* (SVU - International Journal of Medical Sciences, 2022)
Background: A popular presenting symptom for a number of disorders is lymphadenopathy. Malignant and non-malignant lymphadenopathy differentiation has major clinical and therapeutic advantages. Objectives: Assess the efficacy of doppler ultrasound in differentiating malignant and non-malignant lymphadenopathy. Patients and methods: this study was done on 20 patients with clinically enlarged one or more axillary or cervical lymph nodes of both sexes and of different age groups.The lymph nodes were subjected to sonographic and Doppler studies, which were correlated with pathological diagnoses obtained by lymph node biopsy. Results: At cut off point of 1.36, pulsatile index had 75% sensitivity and 85% specificity with overall diagnostic accuracy was 80% in diagnosis of malignant lymphadenopathy. At cut off point of 0.65, resistive index had 86% sensitivity and 92.3% specificity with overall diagnostic accuracy was 89% in diagnosis of malignant lymphadenopathy. Conclusions: In differentiating benign from malignant lymph nodes, Color Doppler ultrasound plays an important complementary function to ultrasound. This adds to the diagnostic faith that can predict malignancy. If grey scale ultrasound results are equivocal, color doppler is also beneficial, and it increases diagnostic accuracy.